After the Research Turn. Issue 1 (11th December 2020) - Slager, Henk
MaHKUscript's 2020 issue rearticulates the discussion about the situation and position of artistic research. Not only as a critical examination of the findings of the present "Research Decade, " but specifically as a quest for future scenarios and associated parameters and definitions. To give an impetus to such reflection, MaHKUscript will take the conceptualization of a post-research turn as point of departure.